BROCA’S APHASIA SYNTACTICAL STRUCTURES IN TWO YOUTUBE VIDEOS - Shinta Aziez; Purwanti Taman; Brandon John Frederik (Universitas Pamulang, 2023)
Aphasia is a language disorder that is caused by the damage in the language processing areas of the brain, which is most commonly caused by stroke. The main study focus of this research is Broca’s aphasia. Broca’s aphasia is the type of aphasia caused by the damage in Broca’s area – the part of the human brain which function is related with speech production and located in the inferior frontal gyrus of the frontal lobe. Broca’s aphasia is known to impart the sufferers’ ability in expressing their thoughts in the correct syntactical manner. Therefore, this research aims to examine the syntactics of Sarah Scott’s and Mark Paulovich aphasic expressions in videos uploaded in the SymphUK and Mark Paulovich YouTube channels. The researchers utilize the descriptive qualitative method as research methodology, as the existing data are in form of two chosen verbal expressions by Sarah Scott and Mark Paulovich in two videos uploaded in the mentioned two YouTube channels. Moreover, the data analysis itself is done through determining the constituents by using phrase structure analysis as proposed by Fromkin, et al. (2014). The results of the study indicate that the chosen utterances contain the features of Broca’s aphasia, that are mainly visible through the disturbances in producing grammatical words and inflections; in setting of the more complex sentences; and the ordered subject-verb agreement, where in the same time still retain ability to express utterances with conceptual words (‘telegraphic speech’). Therefore, the researchers suggest that further research regarding aphasia is necessary, as a mean to increase our knowledge regarding the disease and human brain, and that the awareness to prevent aphasia and its associated medical conditions are raised among everyone, including the readers.